Growth Mindset and Academic Support as Predictors of Academic Motivation in Female First-Generation Students - Gottschlich, Daniela; Turner, Sarah; Anderson, Michael (Psychology of Woman Journal, 2024)
Objective: The objective of this study was to examine how growth mindset and academic support predict academic motivation among female first-generation university students.Methods and Materials: A correlational descriptive design was employed with 474 participants recruited from multiple Canadian universities. Each participant self-identified as female and first-generation, reporting on validated questionnaires that measured growth mindset, perceived academic support, and academic motivation. Data were analyzed using Pearson correlation and multiple linear regression in SPSS-27. Descriptive statistics, including means and standard deviations, were computed for all variables to determine overall trends in the sample. The assumptions for linear regression—linearity, multicollinearity, normality, and homoscedasticity—were confirmed prior to analysis. Ethical approval was obtained, and informed consent was collected from each participant.Findings: Pearson correlation analyses revealed that both growth mindset (r = .48, p < .01) and academic support (r = .56, p < .01) had significant positive relationships with academic motivation. The multiple linear regression model was statistically significant, F(2, 471) = 138.62, p < .001, explaining 37% of the variance in academic motivation (R² = .37). Growth mindset (β = .29, p < .001) and academic support (β = .38, p < .001) emerged as significant predictors, indicating that higher levels of each factor were associated with greater academic motivation in this sample.Conclusion: The findings underscore the pivotal role of both cognitive and contextual variables in predicting academic motivation among female first-generation students. Interventions that cultivate growth mindset beliefs and bolster academic support could have a substantial impact on enhancing motivation, ultimately promoting academic persistence and success within this demographic.